Studying species definitions for mutual nonexclusiveness - Mccabe, Thomas (Zootaxa, 2008)
In the absence of a single universally accepted species concept, taxonomists rely on working conventions when defining species. One such convention is based on the intuition that no specimen is in more than one existing species: species are disjoint and their definitions should be mutually exclusive. When two species definitions both describe one and the same specimen, the two definitions are not mutually exclusive and do not conform to this assumption. Uncorrected, such nonexclusive species definitions make taxonomic indistinctness. Here the author, after exploring the notion of mutual nonexclusiveness, presents simple ways to revise or replace a pair of currently accepted species definitions if they are found to be mutually nonexclusive. The author shows some possible consequences of not doing so in two important areas of biologic research—species diversity studies, and heterospecific hybridization experiments. There is a semiformal discussion of nonexclusiveness in an appendix.